Modelling of atmospheric turbulence in inhouse rotorcraft simulation tool: characterization and comparison - Cetin, C.; Caliskan, A.; Sansal, K.; Kargin, V. (My University, 2022)
In the present work, integration of an atmospheric turbulence model approximating the von Kármán spectra into the TA Originated Rotorcraft Simulation (TOROS) tool is presented. The integrated atmospheric turbulence content consists of 3D velocity components based on the second order statistics. Prior to the implementation, the model is analyzed in detail. Turbulence model is compared with flight test data along with the helicopter flight dynamics model where the initial trim points and power spectral densities of the helicopter rates are used as validation parameters. The results indicate that injection of the atmospheric turbulence component significantly alter the helicopter control rates representing meaningful agreement with flight test data. In addition, the effect of the different aerodynamic surfaces is also analyzed. The results indicate that turbulence in main rotor is the major contributor to the energy spectrum for the heave and roll rates.